Local Wisdom of Atoni Pah Meto in the Cyberspace of Evangelical church In Timor, Indonesia (Journal of Namibian Studies : History Politics Culture, 2023)
This research intends to describe the using of cyberspace by the Evangelical Church inTimor (GMIT). The focus of this research is local value encounter of atoni pah meto with the reality of globalization. By using a digital ethnographic approach, the conclusion of research is first, GMIT has done an quantifying dialectical, both by GMIT toward local prudence values atoni pah meto and GMIT's response to globalization penetration through cyberspace as the main instrument of digitisation. A second conclusion: GMIT as a church institution has defined and agreed upon a consensus that makes the local virtue of atoni pah meto one of the references to the formulation of the consensus. Thus, local prudence values can permeate the GMIT universe. The third conclusion: in making use of cyberspace, GMIT rules beyond the value of cyberspace merely a digital reality. GMIT has entered cyberculture as a new habitat in its service to the church and the community.